Aggregation dependent fluorescence switching in benzothiazole derivative based H-bonded mesogen. Issue 11 (2nd September 2018) - Chakraborty, Bimal B.; Anwar, Siddique; Das, Saurav; Paul, Satya B.; Mohiuddin, Golam; De, Joydip; Choudhury, Sudip
ABSTRACT: In this work, hydrogen-bonded liquid crystal exhibiting phase dependent fluorescence has been reported. The H-bonded materials were prepared using pyridenyl benzothiazole and alkoxy benzoic acid as H-bond acceptor and donor respectively. The formation of the target materials was confirmed via different spectroscopic technique and their mesogenic behaviour has been studied through polarising optical microscope, differential scanning calorimetry and 2D-X-ray diffraction. The H-bonded mesogenic material showed aggregation dependent fluorescence switching when subjected to transformation from isotropic-nematic-crystalline phase sequence. Computational studies were performed to probe into fluorescence switching behaviour of the mesogenic material. GRAPHICAL ABSTRACT: